PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DESA LEBAKSANGKA KECAMATAN LEBAKGEDONG KABUPATEN LEBAK PROVINSI BANTEN - Salamet; Septiowati, Rini (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of leadership and work discipline on employee performance at the Lebaksangka Village Office, Lebakgedong District, Lebak Regency, Banten Province. The method used is quantitative. The population used in this research was 53 employees with a sampling technique using saturated sampling, namely 53 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that leadership influences employee performance with a coefficient of determination value of 37.1% and the hypothesis test obtained t count > t table or (5.481 > 2.006). Work discipline has a significant effect on employee performance with a coefficient of determination value of 61.2% and hypothesis testing obtained t count > t table or (8.966 > 2.009). Leadership and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 7.042 + 0.178X1 + 0.667X2. The coefficient of determination value is 22.9%. Hypothesis testing obtained a calculated F value > F table or (41.972 > 3.18). Thus, it can be explained that there is a significant simultaneous influence between Leadership and Work Discipline on the Performance of Lebaksangka Village Office Employees, Lebakgedong District, Lebak Regency, Banten Province.